Problem antycznej ekfrazy teatralnej. Część I: Postać - Czerwińska, Jadwiga (Collectanea Philologica, 2018)
Ekphrasis is one of the forms that the Greek tragic dramatists used in their plays. From a dramaturgical point of view it was a very important element of play strictly connected with the conventions of the ancient theater. The examples taken from the Euripidean tragedy will be used to demonstrate the ways the ancient Greek tragedians applied ekphrasis in their works. Their review will start with descriptions, which can be conventionally called the ekphrasis of the theatrical “mask”. The term mask is understood here not sensu stricto as a part of actor’s costume, but as having a reference to what it hides. This type of ekphrasis may be found in visually inaccessible to the public of the Greek theater face of dramatis personae that is hidden behind the mask. It concealed facial expressions, so important to understand the action of the drama itself, as well as the role played by the actor. It is impossible to overestimate the importance of this dramaturgical element as a non-verbal means of communication which harmonizes with the text of play and its action and is crucial to perceive the intended meaning of the actors’ words.